Factor structure of the parent-rated strengths and difficulties questionnaire in a sample of Canadian children from military families - Coulthard, Julie; Sudom, Kerry (Frontiers in Psychology, 2023)
The Strengths and Difficulties Questionnaire is a 25-item screening tool designed to measure the emotional and behavioral well-being of children. It includes five subscales including Emotional Symptoms, Conduct Problems, Peer Problems, Hyperactivity-Inattention and Prosocial Behavior. While the Strengths and Difficulties Questionnaire has been studied extensively on a global scale, it has not yet been evaluated among Canadian children from military families. This study used data collected from spouses and partners of Canadian Armed Forces members who completed a questionnaire assessing their quality of life, including the Strengths and Difficulties Questionnaire for respondents with children aged 3-16 years (N=651). Using two independent randomized samples drawn from the overall group of respondents, the factorial structure was studied using exploratory factor analysis (n=323) and confirmatory factor analysis (n=328). Results of this study provide evidence for the factorial validity of the parent-rated Strengths and Difficulties Questionnaire for a sample of children from military families. Specifically, the exploratory factor analysis and confirmatory factor analysis supported the original proposed five-factor solution (CFI = .84; TLI = .82; SRMR = .073; RMSEA = .065) with good internal reliability of the Total Difficulties Scale and subscales. Overall, the results of this study were found to align with past research findings on the Strengths and Difficulties Questionnaire and support the future utility of this tool in assessing the well-being of Canadian children from military families.